Deconstructing the microbial necromass continuum to inform soil carbon sequestration. (18th February 2022) - Buckeridge, Kate M.; Creamer, Courtney; Whitaker, Jeanette
Abstract: Microbial necromass is a large, dynamic and persistent component of soil organic carbon, the dominant terrestrial carbon pool. Quantification of necromass carbon stocks and its susceptibility to global change is becoming standard practice in soil carbon research. However, the typical proxies used for necromass carbon do not reveal the dynamic nature of necromass carbon flows and transformations within soil that ultimately determine necromass persistence. In this review, we define and deconstruct four stages of the necromass continuum: production, recycling, stabilization and destabilization. Current understanding of necromass dynamics is described for each continuum stage. We highlight recent advances, methodological limitations and knowledge gaps which need to be addressed to determine necromass pool sizes and transformations. We discuss the dominant controls on necromass process rates and aspects of soil microscale structure including biofilms and food web interactions. The relative importance of each stage of the continuum is then compared in contrasting ecosystems and for climate change drivers. From the perspective of the continuum, we draw three conclusions to inform future research. First, controls on necromass persistence are more clearly defined when viewed through the lens of the continuum; second, destabilization is the least understood stage of the continuum with recycling also poorly evidenced outside of a few ecosystems; and third, the response of necromass process rates to climate change is unresolved for most continuum stages and ecosystems. Future mechanistic research focused on the role of biotic and abiotic soil microscale structure in determining necromass process rates and the relative importance of organo–mineral and organo–organo interactions can inform necromass persistence in different climate change scenarios. Our review demonstrates that deconstructing the necromass continuum is key to predicting the vulnerability and persistence of necromass carbon in a changing world. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.